Preliminary study of the gonadal development of "imbaw laki", Anodontia edentula (Linne, 1758). - Yu, Rosito D. Jr. (1997.)
The study aimed (1) To gather preliminary information on the sexual maturation of Anodontia edentula by histological descriptions of the gonad, (2) To correlate shell size with stage of gonadal development , and (3) To determine the size range at which sexual maturity is attained. (p)Eighty-one mud clams were obtained from Panubulon, Nueva Valencia, Guimaras and shell lenght, width, height, body and gonad weight were measured. The mud clams were categorized into Subclass 4 (60-70 mm) based on shell lenght. Three to five gonads were randomly selected from each subclass, processed histologically into serial slide sections, and examined under the microscope. , Results suggest that Anodontia edentula is hermaphroditic and protandric such that the testicular region is sexually mature at shell lengths of 30mm or less, and the ovarian region at shell lengths of 50-60 mm. The GSI is inversely related to shell lenght such that as shell length increased, GSI decreased. This attributed to the shrinkage of tissue as spawning and release of gametes progress.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Imbaw; Anodotia Edentula